Interactive Books for Problem Solving: Improving Cognitive Skills in Early Childhood Education - Linda Komala; Besse Nirmala; Ika Juhriati; Durrotunnisa Durrotunnisa (Universitas Al-Hikmah Indonesia, 2026)
This development highlights children's cognitive ability issues, particularly their problem-solving abilities which are below average for the five to six age group. This research is intended to create a practical and efficient interactive book medium. This development applies the R&D method. The procedures passed include the identification phase, design, development stage, which is then followed by implementation and thorough testing (Evaluation)). The number of research subjects was 15 children. In order to determine the media’s viability and efficacy, data analysis techniques werw employed, utilizing both quantitative and descriptive qualitative methods. In addition to user trials, product validation involves three specialists: material, language, and media. 'Highly Valid' is the decision given for this interactive book medium, which receives a 100% score in the validation process. N-Gain was also determined to be 88% in the efficacy test. The effectiveness criterion is >76%, so this figure is considered effective and belongs to the high group. Since this interactive book media has the potential to greatly enhance student learning result, it is extremely practical to employ it as a learning activity support.